Математическое моделирование осветления суспензии в динамическом слое - Поляков, В.Л. (Доповіді НАН України, 2019)
Сформулирована и строго решена нелинейная нестационарная задача безотрывного поверхностного фильтрования при постоянном перепаде давлений на неподвижной и подвижной границах динамического слоя. Полученное в параметрической форме решение позволяет надежно прогнозировать изменения во времени качества фильтрата и производительности установки поверхностного фильтрования. На ряде примеров проанализировано влияние сорбционных свойств фильтрующего материала, автокатализа, темпа формирования динамического слоя на важнейшие характеристики фильтрования. Сформульовано і точно розв'язано нелінійну нестаціонарну задачу безвідривного поверхневого фільтрування при постійному перепаді тисків на нерухомій і рухомій границях динамічного шару. Отриманий у
параметричній формі розв'язок дозволяє надійно прогнозувати зміни у часі якості фільтрату і продуктивності установки поверхневого фільтрування. На ряді прикладів проаналізовано вплив сорбційних властивостей фільтруючого матеріалу, автокаталізу, темпу формування динамічного шару на основні характеристики фільтрування. A non-linear non-steady task of undetachable cake filtration at a constant pressure difference at moving and
stationary cake layer boundaries is formulated and solved exactly. Sorption and conductivity possibilities are
described by arbitrary functions. The solution obtained in the parametric form enables one to predict reliably
chan ges in time of the filtrate quantity and productivity of a cake filtration installation. The effects of layer sorption
pro perties, autocatalysis, and rate of cake formation on the main filtration characteristics are analyzed for a
number of test examples. It is established that a considerable decrease in the suspended substance content in a
filtrate, and filtration rate occurs during a short time, and the deposition is distributed along the dynamic
layer height essentially unevenly with the maximum at its exit.